Spirit of Place Analysis of Bandar Lampung Teluk Market as The Act of Heritage Conservation - Ishar S I; Sadad I (International Conference on Engineering and Technology Development (ICETD), 2017)
Bandar Lampung Teluk Market Area is an important areaforming BandarLampung city in the past. This area is an economic milestone in the city and is known as astrategic trading area since 1839. Its position which directly tangent to the coastalareasinvites migrants from all over the country to trade. Starting from the superior potentialof seafood, Teluk Marketoffers an increasingly diverse variety of commodities. Startingfrom the needs of food, clothing to the entertainment. Cultural diversity of people aroundthe Teluk Market coming from all over the country offers a multi-ethnic nuance and createsvariety of unique food whichfinally became the famous culinary in the city until now.Notonly known as a trading center, Teluk Market is also known as the lifestyle center in itsheyday. These potentials leave a nostalgic atmosphere to the area. The area is surroundedby the architecture of Dutch heritage buildings, old pagoda, and old shops that aged over 60years. But as the era progressed, precisely since 1984 where Tanjung Karang and TelukBetung merged into a single city (known as Bandar Lampung), this area is getting lessinterested by the visitors. Teluk Market is seen as an untapped old trading area. Thedevelopment and construction of Bandar Lampung City concentrates more on TanjungKarang which is now increasingly filled with modern shopping centers. Teluk Marketcontinued to fade in popularity compared to modern mall markets.Therefore, this studyaims to rediscover the spirit of place in the Teluk Market area and then introduce it back tothe community as one of the identity of Bandar Lampung City. This research will analyzethe spirit of place of this region by way of; 1) analyzing the spirit of place in terms of thearchitecture of the old buildings by identifying the style and age of the buildings; 2)analyzing the perceptions of surrounding communities. This research will result buildingtypology and community perception of Teluk Market which can be used as a foundation inconserving and developing Teluk Market area as a heritage area